The Curriculum of Love in Pesantren - Burhanuddin, Hamam; Hamidah, Aida (Proceedings of Annual Conference for Muslim Scholars, 2025)
This article explores the implementation of a "curriculum of love" (kurikulum cinta) in Islamic boarding schools (pondok pesantren) as a transformative model of humanist-religious education for the millennial generation. The study highlights how pesantren, as traditional yet dynamic Islamic educational institutions, integrate values of love, compassion, tolerance, and humanity into their curricula. Using a qualitative descriptive approach, this study analyzes educational practices such as religious rituals, character formation, and social engagement programs that embed the values of rahmah (compassion) and mahabbah (love). The findings indicate that pesantren have successfully contextualized local wisdom and Islamic teachings to nurture inclusivity, empathy, and peace-building among students. This curriculum model not only strengthens students’ religious identity but also equips them with global humanist values necessary for navigating contemporary challenges. In conclusion, the "curriculum of love" in pesantren reflects an innovative synergy between tradition and modernity, offering a sustainable model of education for shaping tolerant, ethical, and globally aware Muslim youth